Phenolic compounds as antidiabetic, anti‐inflammatory, and anticancer agents and improvement of their bioavailability by liposomes - Tatipamula, Vinay Bharadwaj; Kukavica, Biljana (Cell biochemistry and function, 2021)
Phenolic compounds, widespread in plants, are a necessary part of the human regimen due to their antioxidant and pro‐oxidative properties. Naturally, phenolics structurally range from a very simple phenolic molecule moiety to an intricate polymer. For decades, phenolic compounds have gained pronounced attention because of their protective effects against degenerative disorders such as inflammation, diabetes and cancer. Physico‐chemical properties (eg, solubility) restricted their bioactivity and also limited their usage as nutraceutical ingredients. However, encapsulation technology like liposomal formulations has been developed for the delivery of phenolic compounds without affecting their original aesthetic and organoleptic property. Hence, this review outlines the antioxidant and pro‐oxidative properties of phenolic compounds and focuses on biological activity reports of flavonoids and phenolic acids as antidiabetic, anti‐inflammatory and anticancer agents. Also, the delivery applications of phenolic compounds as liposomes are discussed with few examples.